2009
DOI: 10.1021/nl803676e
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the 3D Nanostructure of a Polymer Solar Cell by Electron Tomography

Abstract: Electron tomography has been used for analyzing the active layer in a polymer solar cell, a bulk heterojunction of an alternating copolymer of fluorene and a derivative of fullerene. The method supplies a three-dimensional representation of the morphology of the film, where domains with different scattering properties may be distinguished. The reconstruction shows good contrast between the two phases included in the film and demonstrates that electron tomography is an adequate tool for investigations of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 20 publications
2
89
0
Order By: Relevance
“…13). 81,82 A clear picture of phase separation governed by these parameters was obtained. TEM showed that different kinds of fullerene derivatives had a strong effect on the morphology, which was explained by the differences in their solubilities.…”
Section: Polyfluorene-based Polymermentioning
confidence: 91%
“…13). 81,82 A clear picture of phase separation governed by these parameters was obtained. TEM showed that different kinds of fullerene derivatives had a strong effect on the morphology, which was explained by the differences in their solubilities.…”
Section: Polyfluorene-based Polymermentioning
confidence: 91%
“…Input morphology can either be from experimental observation [21,22,23] or numerical simulations [24,25,26]. We demonstrate how the constructed suite of morphology descriptors can be employed to characterize experimentally acquired morphology.…”
Section: Application To Analysis Of Bhj Morphologymentioning
confidence: 99%
“…• Progress in experimental characterization [21,22,23] and computational modeling [24,25,26] now allow insitu and in-silico 3D reconstruction and imaging of the thin film morphology with unprecedented accuracy and resolution. A computational framework capable of constructing morphology descriptors efficiently, can enable rapid and effective assimilation of large morphology (both temporal and spatial) data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Defocusing is typically used to enhance contrast in bright-field TEM imaging, and great care must be taken to distinguish between genuine features and artefacts due to the defocus. Despite these difficulties, beautiful three-dimensional images have been obtained of polymer:fullerene and polymer:ZnO films [27][28][29].…”
Section: Imaging Nanostructure In Bulk Heterojunctionsmentioning
confidence: 99%